Quantifying the numeric and linguistic magnitude of perceived risk in e-commerce interactions for RDSS - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh Khadeer; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
In an e-commerce business interaction, the risk assessing agent by analyzing the possible level of perceived risk beforehand can make an informed decision of its future course of interaction with an agent. The perceived risk in the context of an e-commerce business interaction is a multidimensional construct which is the combination of its subcategories. In this paper we propose a methodology by which the risk assessing agent can ascertain the numeric and linguistic level of perceived risk in an interadion by combining its different subcategories.